Comparative Analysis of Ontology Scientism and Religious Philosophy in XX Century - Snitko, D. Yu. (Anthropological Measurements of Philosophical Research, 2012)
Тhis article considered the ontological aspects of philosophy by XX century’s western scientism and religious metaphysics. Specially attention concentrated of the empirical and metaphysical components of the seontological paradigms, and also of the problem of ontological relativity and relations with the anthropological investigations.